2012
DOI: 10.1063/1.4742194
|View full text |Cite
|
Sign up to set email alerts
|

Band-edge transitions in hexagonal boron nitride epilayers

Abstract: Effects of scattering on two-dimensional electron gases in InGaAs/InAlAs quantum wells J. Appl. Phys. 112, 023713 (2012) High efficiency ultraviolet emission from AlxGa1−xN core-shell nanowire heterostructures grown on Si (111) by molecular beam epitaxy Appl. Phys. Lett. 101, 043115 (2012) Current transport in nonpolar a-plane InN/GaN heterostructures Schottky junction J. Appl. Phys. 112, 023706 (2012) Superlinear electroluminescence due to impact ionization in GaSb-based heterostructures with deep Al(As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 28 publications
(58 reference statements)
2
60
0
Order By: Relevance
“…Based on the intense photoluminescence at low temperature from epitaxial hBN layers deposited on sapphire substrates, Majety et al [16] also supported the finding that hBN is a direct bandgap semiconductor. Using state-of-the art all-electron GW approximation, Arnaud et al [22] asserted hBN is in fact an indirect band gap semiconductor.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Based on the intense photoluminescence at low temperature from epitaxial hBN layers deposited on sapphire substrates, Majety et al [16] also supported the finding that hBN is a direct bandgap semiconductor. Using state-of-the art all-electron GW approximation, Arnaud et al [22] asserted hBN is in fact an indirect band gap semiconductor.…”
Section: Discussionsupporting
confidence: 48%
“…The laser beam was focused onto the sample surface with a lens. The PL signal was collected and dispersed by a monochromator (1.3 meters), and then detected by a microchannel-plate photomultiplier tube together with a single photon-counting system [16].…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10] Epitaxial h-BN layers with high optical qualities can be achieved, 7,20 but these materials generally lack the intrinsic FX transitions above 5.7 eV due to the presence of native and point defects. 7,20 Most recent studies have suggested that the D-series emission lines are due to the recombination of excitons bound to deep acceptors formed by carbon impurities occupying the nitrogen sites, and h-BN epilayers exhibiting pure intrinsic FX emission can be obtained by growing the materials under high ammonia flow rates. 21 However, the detailed features of the FX transitions in h-BN epilayers are distinctly different from those in h-BN bulk crystals, 21 which is what remains to be investigated and understood.…”
mentioning
confidence: 99%
“…A deep UV time-resolved PL system was utilized to probe the emission properties. 13,20 The system consists of a frequency quadrupled 100 fs Ti:sapphire laser providing an excitation photon energy of 6.28 eV and a monochromator (1.3 m) in conjunction with a single photon counting detection system providing a timeresolution of 20 ps and a streak camera system providing a time-resolution of 2 ps.…”
mentioning
confidence: 99%
“…Thus, it is likely that the material has direct band gap of around 6 eV. In addition, it was shown that h-BN has higher luminescence efficiency than AlN [23]. Thus h-BN could be employed as a deep UV emitter and detector competing with AlN.…”
Section: Properties and Applications Of Sp 2 -Bnmentioning
confidence: 99%